(untitled) (Mongolian Journal of Agricultural Sciences, 2014)
Tracheal and cloacal swabs were collected from a total of 195 juvenile shorebirds in the area in 2012 in Eastern Hokkaido, Japan. Viruses showing hemagglutination activity were successfully recovered from 28 bird samples. All viruses were identified as AIV by RT-PCR to detect viral M genes of influenza A virus, and were determined to be H4N7 subtype by RT-PCR for subtyping of AIV. Phylogenic analysis of the matrix (M) genes of 12 strains selected on the basis of their different places and date of surveillance. The M genes of 12 strains belonged to the Eurasian Lineages. DOI: http://dx.doi.org/10.5564/mjas.v11i2.207 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.7-15